Encountering aborigines a case study: anthropology and the Australian aboriginal. - Burridge, Kenelm (Pergamon frontiers of anthropology series, PFAS-1., 1973)
Encountering Aborigines: A Case Study: Anthropology and the Australian Aboriginal details the concerns in contemporary anthropological research of aboriginal Australians.